Level of employee job satisfaction From a food factory in northwest Mexico - Márquez Chávez, Karla; Cornelio Muñoz, Fany; Linares Gómez, Víctor (Unaciencia, Revista de Estudios e Investigaciones, 2023)
Job satisfaction is a key piece to form an effective work team in the company, which is projected in greater productivity. The general objective of this study is to determine the degree of job satisfaction of the employees of a Food factory. For which it was necessary to analyze the degree of satisfaction in each of its dimensions, relate job satisfaction with the degree of schooling and the time of working in the company. The research was quantitative-descriptive. The population was 52 employees of the food factory, of whom 40 were surveyed. For data collection, an instrument of 37 items was applied. It was concluded that the collaborators of the food factory do not have a degree of satisfaction higher than 80% of the scale. Demographic variables such as education, time in the company and gender are not variables that influence employee satisfaction.
Keywords: Array; Array; Array